Skills of teaching the Qur’an between memorization and contemplation: a methodical study - Elatrash, Radwan Jamal Yousef; Ahmad, Nadzrah; Gasmelsid, Saadeldin Mansour; Abul Lais, Mohammed (IIUM Press, International Islamic University Malaysia, 2018)
The Qur’an with precise method and style has become an integral focus in understanding the meaning and gist of Qur’anic verses. Teachers used different methods of teaching which involves various skills. Both contemplation and recitation skills became major focus of teaching the Qur’an. This study intends to assess the intensity of using these skills among teachers and to examine methods of inculcating reflection of the Qur’anic message among students. It also seeks to evaluate these methods and suggest with best possible ways to combine both methods in Qur’anic teaching. The study is qualitative in nature and involves several collective methods such as inductive method, descriptive analytical as well as comparative analysis.